Chemical Profiling, Antioxidant, Anticholinesterase, and Antiprotozoal Potentials of Artemisia copa Phil. (Asteraceae) - Larrazábal-Fuentes, María José; Fernández-Galleguillos, Carlos; Palma-Ramírez, Jenifer; Romero-Parra, Javier; Sepúlveda, Kevin; Galetovic, Alexandra; González, Jorge; Paredes, Adrián; Bórquez, Jorge; Simirgiotis, Mario J.; Echeverría, Javier (Frontiers in Pharmacology, 2020)
Artemisia copa Phil. (Asteraceae) (known as copa-copa) is a native species of Chile used as an infusion in traditional medicine by Atacameños people in the Altiplano, highlands of northern Chile. In this research, we have investigated for the first time the cholinesterase inhibition potential against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE), and the chemical profiling of the infusions prepared from the aerial parts of A. copa by high resolution spectrometry. In addition, the antioxidant (DPPH, FRAP, and ORAC) and antiprotozoal activity were tested. Artemisia copa showed good inhibitory activity against AChE and BChE (3.92 ± 0.08 µg/mL and 44.13 ± 0.10 µg/mL). The infusion displayed a total phenolics content of 187.4 ± 2.9 mg gallic acid equivalents/100 mL and total flavonoid content of 6.6 ± 0.2 mg quercetin equivalents/100mL. Additionally, trypanocidal activity against Trypanosoma cruzi was found (LD50 of 131.8 µg/mL). Forty-seven metabolites were detected in the infusion of A. copa including several phenolic acids and flavonoids which were rapidly identified using ultrahigh performance liquid chromatography orbitrap mass spectrometry analysis (UHPLC-Orbitrap-MS) for chemical profiling. The major compounds identified in the infusions were studied by molecular docking against AChE and BChE. The UHPLC-MS fingerprints generated can be also used for the authentication of these endemic species. These findings reveal that A. copa infusions can be used as beverages with protective effects.